Frontal‐Photopolymerization of Fully Biobased Epoxy Composites. Issue 6 (7th January 2022) - Noè, Camilla; Hakkarainen, Minna; Malburet, Samuel; Graillot, Alain; Adekunle, Kayode; Skrifvars, Mikael; Sangermano, Marco
Abstract: The radical‐induced cationic frontal photopolymerization (RICFP) of fully biobased epoxy composites is successfully demonstrated. This curing strategy considerably reduces the curing time and improves the efficiency of the composite fabrication. Two different natural fiber fabrics made of cellulose and flax fibers are embedded in two epoxy matrices, one derived from vanillin (diglycidylether of vanillyl alcohol‐DGEVA) and the other from petroleum (3, 4‐epoxycyclohexylmethyl 3, 4‐epoxycyclohexanecarboxylate‐CE). After RICFP the composites are characterized by means of dynamic mechanical thermal analysis and tensile tests. The mechanical properties improved with increasing fiber content, confirming a strong adhesion between the matrix and the reinforcing fiber fabrics, which is further evidenced by scanning electron microscopy analyses of the fracture surfaces. Furthermore, these fully bio‐based composites possess comparable or even higher mechanical strength compared with the corresponding epoxy composites fabricated with conventional CE resin. A promising facile route to high‐performing natural fiber‐biobased epoxy resin composites is presented. Abstract : Fully biobased composites are successfully cured via "green" and fast frontal photopolymerization technique. Two different natural fiber fabrics made of cellulose and flax fibers are selected as reinforcing agents for a biobased epoxy resin deriving from vanillin alcohol. The thermo‐mechanical properties of the composites increase as the fiber content increases confirming a good adhesion between the matrix and the fiber fabrics.